2023
DOI: 10.1002/pro.4612
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the structural heterogeneity of proteins by native mass spectrometry

Abstract: A single gene yields many forms of proteins via combinations of posttranscriptional/posttranslational modifications. Proteins also fold into higher‐order structures and interact with other molecules. The combined molecular diversity leads to the heterogeneity of proteins that manifests as distinct phenotypes. Structural biology has generated vast amounts of data, effectively enabling accurate structural prediction by computational methods. However, structures are often obtained heterologously under homogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 187 publications
0
2
0
Order By: Relevance
“…Native MS provides species distributions of conformers and supramolecular complexes upon gentle desolvation and ionization, yielding values of stoichiometry and solvent accessible surface area (Tamara et al, 2022). Combination with IM introduces an additional dimension in ion separation and analysis, detecting structural heterogeneity even within each charge state and measuring rotationally-averaged, collisional cross-section (CCS) (Kaltashov et al, 2022;Santambrogio et al, 2022, Christofi andBarran, 2023;Reid et al, 2023).…”
Section: Methodological Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Native MS provides species distributions of conformers and supramolecular complexes upon gentle desolvation and ionization, yielding values of stoichiometry and solvent accessible surface area (Tamara et al, 2022). Combination with IM introduces an additional dimension in ion separation and analysis, detecting structural heterogeneity even within each charge state and measuring rotationally-averaged, collisional cross-section (CCS) (Kaltashov et al, 2022;Santambrogio et al, 2022, Christofi andBarran, 2023;Reid et al, 2023).…”
Section: Methodological Approachesmentioning
confidence: 99%
“…This rich structural information can guide particle classification in cryo-EM/ET, ensemble deconvolution by NMR and computational modelling by experimental constraints. Structural heterogeneity deriving from PTMs, ligand binding and protein assemblies can also be described (Kaltashov et al, 2022;Reid et al, 2023). MS methods can in principle be implemented in a time-resolved mode on the millisecond scale (even microsecond for FPOP), although such instrumental setups are still not widespread (Lento and Wilson, 2022).…”
Section: Methodological Approachesmentioning
confidence: 99%
“…The rapid developments of novel proteomic technologies and applications has led to the establishment of many specialized approaches focusing on targeted biomarker proteomics [63,64], clinical proteomics [65,66], drug discovery and pharmaco-proteomics [67][68][69], proteogenomics [70,71], membrane proteomics [72,73], extracellular matrix proteomics [74,75], native proteomics [76][77][78], thermal proteome profiling [79], the analysis of protein conformations and interactions via chemical cross-linking MS [80,81] and subcellular/organelle proteomics [82,83]. The more recently developed discipline of native MS focuses on the detailed top-down characterization of structural heterogeneity in protein isoforms under non-denaturing conditions, making this approach an important part of structural cell biology [84,85].…”
Section: The Importance Of Proteomics and The Concept Of Proteoforms ...mentioning
confidence: 99%
“…24,25 However, few studies have reported top-down analysis of glycoproteins, which requires advanced activation techniques, 26 advanced separation techniques 27 , or may utilize partial enzymatic deglycosylation [28][29][30] to mitigate the analytical challenge presented by glycan heterogeneity which creates an overlap of glycoproteoforms in the m/z domain. 31 One of the major ongoing challenges in the top-down proteomics workflow is the successful separation of glycoproteins. Traditional reversed phase liquid chromatography (RPLC) methods (C18, C4, PLRP, and others) are suitable for the separation of cleaved permethylated glycans, 32 small glycopeptides, [33][34][35] and some intact proteins, 21 but do not always provide sufficient resolution of larger glycans and glycosylated proteins.…”
Section: Introductionmentioning
confidence: 99%